APPLICATION OF COMPUTER PROGRAMMES IN RESEARCH PROJECTS AND TEACHING - Ptak, Paweł (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Integrated software packages, such as National Instruments Multisim or DasyLab can be successfully applied in developing research projects and in teaching. Thanks to their intuitive use and wide potential they can be utilised as support for simulation and other programmes. They are also often applied for comparative analysis of real measurement results with computer simulations. Apart from that, they can also be useful in a research or experimental lab.